Optimizing Business Process To Government Using Business Process Improvement (BPI) and Bizagi Modeler (Case Study: PT. XYZ) - Pangga Cahyo Dwiyono; Murhadi Murhadi; Wahju Tjahjo Saputro; Miftahul Huda; Matthew Nepomuceno (Justek : Jurnal Sains dan Teknologi, 2026)
Business to Government (B2G) processes frequently suffer from inefficiencies caused by manual workflows and limited system integration. This study aims to enhance B2G business process performance at PT XYZ by applying the Business Process Improvement (BPI) approach using Business Process Model and Notation (BPMN) implemented through Bizagi Modeler. The research methodology involves analysing the existing process, designing an optimized process model, and conducting performance simulations based on processing time, operational costs, data accuracy, delay risk, and institutional satisfaction. The results indicate significant improvements, including a 41.7% reduction in processing time, a 26.7% decrease in operational costs, a 90% increase in data accuracy, a 40.9% reduction in delay risk, and an 85% improvement in institutional satisfaction. These findings demonstrate that the integration of BPI and BPMN effectively improves the efficiency and quality of B2G business processes in government procurement.